Répartition spatiale de l’industrie grecque - Vincent Gouzi (Cahiers Balkaniques)
In the debate about Athens, as a capital in crisis, we thought that the strong feeling of crisis has to be substantiated by a few numbers. We can see that the crisis causes deep changes in the structures of the industrial activities, and that will be our first theme. How these changes are translated in the Greek space will be our second subject, and at the end, we’ll see a few questions that arise from our approach to the subject.